Room-temperature highly sensitive and selective NH3 gas sensor using vertically aligned WS2 nanosheets. (22nd January 2023) - Sharma, Shivani; Saini, Rajan; Gupta, Govind; Late, Dattatray J
Abstract: Here, we report the room temperature (35 °C) NH3 gas sensor device made from WS2 nanosheets obtained via a facile and low-cost probe sonication method. The gas-sensing properties of devices made from these nanosheets were examined for various analytes such as ammonia, ethanol, methanol, formaldehyde, acetone, chloroform, and benzene. The fabricated gas sensor is selective towards NH3 and exhibits excellent sensitivity, faster response, and recovery time in comparison to previously reported values. The device can detect NH3 down to 5 ppm, much below the maximum allowed workspace NH3 level (20 ppm), and have a sensing response of the order of 112% with a response and recovery time of 54 s and 66 s, respectively. On the other hand, a sensor made from nanostructures has a bit longer recovery time than a device made from nanosheets. This was attributed to the fact that NH3 molecules adsorbed on the surface site and those trapped in between WS2 layers may have different adsorption energies . In the latter case, desorption becomes difficult and may give rise to slower recovery as noticed. Further, stiffened Raman modes upon exposure to NH3 reveal strong electron-phonon interaction between NH3 and the WS2 channel. The present work highlights the potential use of scaled two-dimensional nanosheets in sensing devices and particularly when used with inter-digitized electrodes, may offer enhanced performance.